Multimodality Imaging of the Peripheral Venous System - Diana Gaitini (International Journal of Biomedical Imaging)
The purpose of this article is to review the spectrum of image-based diagnostic tools used in the investigation of suspected deep vein thrombosis (DVT). Summary of the experience gained by the author as well as relevant publications, regarding vein imaging modalities taken from a computerized database, was reviewed. The imaging modalities reviewed include phlebography, color Doppler duplex ultrasonography (CDDUS), computerized tomography angiography (CTA) and venography (CTV), magnetic resonance venography (MRV), and radionuclide venography (RNV). CDDUS is recommended as the modality of choice for the diagnosis of DVT. A strategy combining clinical score and D-dimer test refines the selection of patients. Phlebography is reserved for discrepant noninvasive studies.